Research on adaptive beacon message broadcasting cycle based on vehicle driving stability. Issue 2 (7th January 2020) - Zhang, Yuejin; Wang, Meng; Wang, Juan; Du, Fei; Hu, Yong; Yu, Meng; Li, Guanghui; Zhan, Aiyun
Summary: Ensuring smooth communication by fixed‐cycle message beaconing in vehicular environments is necessary to address vehicles safety. However, fixed‐cycle beacon messages cannot accommodate the characteristics of fast vehicle speeds and variable network topologies and can cause problems such as channel congestion when traffic density is too high. Therefore, in order to realize safe and reliable information transmission between vehicles, this paper proposes a strategy for adaptive update of beacon message cycle based on vehicle driving stability. It is based on two rules: one is that the vehicle position prediction error is defined as an unstable vehicle, and the small error is defined as a stable vehicle; and the other is that the adaptive beacon message cycle is ranged, which is determined according to the channel load capacity. The experimental results show that the strategy can effectively avoid the channel congestion problem and improve the driving safety of the vehicle. Compared with the fixed‐cycle beacon message, the communication delay is reduced by about 10%, the packet loss is reduced by about 22%, and the energy consumption is reduced. Abstract : This paper proposes a strategy for adaptive update of beacon message cycle based on vehicle driving stability. It is based on two rules: one is that the vehicle position prediction error is defined as an unstable vehicle, and the small error is defined as a stable vehicle; And the other is that the adaptive beacon message cycle is ranged, which is determined according to the channel load capacity.